2017
DOI: 10.1177/1363460717737489
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s just more, you know, natural’: The perceptions of men who buy sex in an emerging street sex market

Abstract: Despite recognition that a greater understanding of men who buy sex in illicit street sex markets is required for a holistic view of street sex work, research focused on this group remains scarce. The authors of this article recognize buyers of illicit sex as key players in the socio-spatial construction of street sex markets, and consider their inclusion in research vital to a holistic understanding of a street sex market. The article discusses key findings from interviews conducted with nine men who buy sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Thus, for example, sex tourism in developing countries is often characterized by open-ended and enduring relationships between sex tourists and local WPS, which seldom facilitates intimate experiences for MWPWS (Bishop & Limmer, 2018;Prior & Peled, 2019). However, street-based SFP is usually referred to by MWPWS in straightforward terms of strictly sexual experiences (Durant & Couch, 2019). Moreover, some MWPWS prefer to become regular clients of a specific woman, whom they pay for sex in indoor settings (Sanders, 2008)-while other MWPWS enjoy the rush and excitement of switching between multiple WPS at varying locations (Plantin, 2020).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…Thus, for example, sex tourism in developing countries is often characterized by open-ended and enduring relationships between sex tourists and local WPS, which seldom facilitates intimate experiences for MWPWS (Bishop & Limmer, 2018;Prior & Peled, 2019). However, street-based SFP is usually referred to by MWPWS in straightforward terms of strictly sexual experiences (Durant & Couch, 2019). Moreover, some MWPWS prefer to become regular clients of a specific woman, whom they pay for sex in indoor settings (Sanders, 2008)-while other MWPWS enjoy the rush and excitement of switching between multiple WPS at varying locations (Plantin, 2020).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…Klein et al (2009), who studied more than 500 Canadian male participants in a prostitution offender program, reported similar results. Although they did not specifically inquire about violence, Durant and Couch (2019) reported that the nine Australian street sex work customers they interviewed engaged in ongoing, friendly contact with the workers from whom they bought sex. Nonetheless, the stratification of violence across sex work sectors suggests that consumers of particular forms of sex work may be more violent (Weitzer, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, "companionship, emotion, and relationships are important and desired aspects of the exchange for some clients" (Milrod and Monto, 2012: 805), with the Girl Friend Experience, a service that mimics aspects of non-commercial relationships such as kissing, companionship, romance and reciprocal pleasure, being a popular and sought out service. A desire for a more 'authentic' encounter is not only limited to off street sex work; Durant and Couch (2019) found that some Australian clients prefer to buy sex from street sex workers in their local area as street-based sex workers were more natural with their dress and demeaner mirroring the non-commercial, in comparison to the staged and sterile brothel environment. In addition, abolitionist accounts neglect the fact that sex workers make 'demands', such as determining what is, and is not available to clients.…”
Section: Initial Work Bymentioning
confidence: 99%
“…However, despite such challenges a variety of successful projects about male clients have been undertaken, using a range of methods for access, recruitment and data collection. These have included using sex worker accounts or referrals (Lever and Dolnick, 2000;O'Connell Davidson, 1996;Shumka et al, 2017); working through sexual health clinics (Ward et al, 2005); advertising in brothels or training brothel staff to conduct surveys (Birch, 2015;Plumridge et al, 1997;Xantidis and McCabe, 2000); undertaking on-street interviews (McKeganey and Barnard, 1996); using media advertisements (Birch 2015;Grenz, 2005); advertising in sports clubs (Chen, 2017); drawing on large scale national survey data (Monto, 1999;Jones et al, 2014;Joseph and Black, 2012); police interviews for secondary data (Sharpe, 1998); ethnographies of sex work spaces (Durant and Couch, 2019;Hoigard and Finstad, 1992); using data gathered from clients on prevention or education programmes (Joseph and Black, 2012;Wahab, 2006); content analysis of commercial sex websites (Horswill and Weitzer, 2018;Soothill and Sanders, 2005;Earle and Sharp, 2008;Holt and Blevins, 2007;Milrod and Monto, 2012;Pettinger 2011;Pruitt and Krull, 2011); engaging with the online sex work community to recruit for participants (Birch et al, 2017;Jin and Xu, 2016;Jones and Hannem, 2018;Milrod and Monto, 2012;Sanders, 2008a); and advertising via non-sex work specific classified adverts (Atchison and Burnett, 2016;Huysman, 2018).…”
Section: Recruitment and Participantsmentioning
confidence: 99%